Modified Pumpkin Flour Using Hydrogen Rich Water with a Microwave Dryer - Gita Indah Budiarti; Ayu Wulandari; Siti Mutmaina; Endah Sulistiawati (Universitas Ahmad Dahlan, 2020)
Pumpkin is a fruit that contains fiber and vitamin A which works to prevent diabetes. Pumpkin's use is not optimal, so it needs innovation for Pumpkin, one of which is to make Pumpkin into flour. Pumpkin does not have gluten, so modification is needed. Modifications used are using hydrogen-rich water with a microwave dryer. Hydrogen-rich water has antioxidant content and is safer for the modification of starch food. The purpose of this study was to determine the physicochemical properties (water content and expandability) and beta carotene levels in HRW-modified flour using a microwave dryer. First, Pumpkin soaked with a variation of time 1, 2, 3, 4, and 5 hours. The optimal results of water capacity and beta carotene levels were obtained at the immersion time of 1 hour by 11%, 7.4 g/g of sample, and 3,164.79 Î¼g/g. The results obtained are higher than the modification of HRW without a microwave dryer.